PENGARUH STRUKTUR DEWAN DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Rifka Eka Ramadhani; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of board structure and ownership structure on the company's financial performance. This research focuses on the financial performance of manufacturing companies because the financial performance of manufacturers, namely the return on equity in the company sector has decreased ROE from 2019 to 2020. The independent variables are the board of directors, board of commissioners, managerial ownership, institutional ownership, and cost of ownership (dividends). Meanwhile, the dependent variable is the financial performance by measuring Return on Equity (ROE). The population and sample in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2018-2021. Samples were taken using a purposive sampling method with predetermined criteria or conditions. The samples obtained from manufacturing companies are 539 companies. This study uses multiple linear regression analysis. The results of research using multiple regression analysis show that the board of commissioners and the cost of ownership (dividend policy) have a positive and significant effect on the company's financial performance, while the board of directors, managerial and institutional ownership have no effect towards the company's financial performance.